The role of nutrition education in the pharmacy curriculum using the example of knowledge about the health benefits of nuts - Stević, Ivana; Milenković, Danijela; Petrović, Ana; Pejčić, Ana; Dodevska, Margarita; Ilić, Marija Prvulović; Ivanović, Nevena (Frontiers in Public Health, 2024)
In recent years, nuts have gained importance because of their nutritional benefits in promoting health and preventing chronic diseases. Despite their recognized role as part of healthy dietary patterns, global consumption is below recommended levels, necessitating an investigation of factors influencing consumption and the impact of nutrition education.ObjectiveTo investigate the attitudes, knowledge and consumption habits of students in Serbia regarding the consumption of nuts and to examine the role and importance of food- or nutrition-related topics in academic curricula in promoting positive attitudes and habits regarding the consumption of nuts among pharmacy students.MethodsAn electronic questionnaire was used to collect data for this cross-sectional study. A total of 509 responses were collected, including 382 from pharmacy students (75.0%) and 127 from non-pharmacy students (25.0%).ResultsAttitudes toward eating nuts were generally positive, with statistically significant differences found between pharmacy students and non-pharmacy students for 10 statements. The knowledge levels differed, with the mean total number of correct answers in the total sample being 3.9 ± 2.5 (R: 0-11, Mdn: 4) out of 13, and there was a statistically significant difference (p < 0.05) between pharmacy students and non-pharmacy students on 8 out of 13 knowledge questions. The study revealed that students obtained information about the health benefits of nuts, mainly from college lectures (51.9%) and mass media (60.9%). More than half of the students (57.8%) expressed a desire for additional information about nuts, which influenced their attitudes significantly more than their level of knowledge.ConclusionThe results showed that pharmacy students had better knowledge and more positive attitudes toward the consumption of nuts compared to non-pharmacy students. Although completion of nutrition-related courses showed some positive influence, this was not statistically significant for most attitudes and beliefs. These findings underscore the potential value of integrating comprehensive nutrition education into pharmacy curricula, as the combination of knowledge and positive attitudes fostered by pharmacy and nutrition education will enable future health professionals to play a critical role in promoting healthier and sustainable eating habits in the population.